INFLATION AND GROWTH IN DEVELOPING ECONOMIES: A TRIBUTE TO PROFESSOR THIRLWALL - Nell, Kevin S. (Investigación Económica, 2023)
ABSTRACT This paper pays tribute to Professor Thirlwall’s substantive work in growth and development economics by providing a review of his book Inflation, Saving and Growth in Developing Economies (1974b) [hereafter ISGD]. Indeed, the hallmark of a good economics book is whether its theoretical content and empirical predictions made several decades ago remain relevant when assessed against more recent evidence. Thirlwall’s ISGD book exhibits all these qualities. It emphasises the importance of distinguishing between different types of inflation. Structural inflation and, to a lesser extent, cost inflation, should be seen as the inevitable outcomes of the growth and development process, whereas demand inflation may act as a direct stimulus to growth, as predicted by the Kaldor-Thirlwall model of forced saving and the inflation tax model. These theoretical insights remain highly relevant in today’s developing economies. Studies tend to show that inflation thresholds, up until the point where the effect of inflation on growth is positive, tend to be higher in developing economies relative to advanced countries, owing to a combination of structural, cost and demand-side sources of inflation. The analysis further argues that inflationary finance of development, as advanced in ISGD, remains a viable development strategy when open-economy constraints are considered. INFLACIÓN Y CRECIMIENTO EN ECONOMÍAS EN DESARRALLO: UN TRIBUTO AL PROFESOR THIRLWALL RESUMEN En este artículo rindo un tributo a la sustancial obra del Profesor Thirlwall sobre la economía del crecimiento y del desarrollo, para lo cual suministro una revisión de su Inflation, Saving and Growth in Developing Economies (1974b) [ISGD en adelante]. En realidad, la calidad de un buen libro de economía consiste en si su contenido teórico y sus predicciones empíricas formuladas hace varias décadas son relevantes cuando se evalúan a la luz de una evidencia más reciente. El libro ISGD de Thirlwall tiene todas estas cualidades. Enfatiza la importancia de distinguir entre diferentes tipos de inflación. La inflación estructural y, en menor medida, la inflación de costos deben considerarse como resultados inevitables del proceso de crecimiento y desarrollo, mientras que la inflación de demanda puede actuar como un estímulo directo al crecimiento, tal como lo pronosticaron el modelo Kaldor-Thirlwall de ahorro involuntario y el de impuesto de inflación. Estos discernimientos teóricos aún son muy relevantes en las economías en desarrollo actuales. Varios estudios muestran que los umbrales de inflación, hasta el punto en que el efecto de la inflación sobre el crecimiento es positivo, tienden a ser mayores en las economías en desarrollo que en los países avanzados, debido a una combinación de fuentes de inflación estructurales, de costos y de demanda. El análisis argumenta, además, que el financiamiento inflacionario del desarrollo, tal como se plantea en ISGD, sigue siendo una estrategia de desarrollo viable cuando se consideran restricciones de economía abierta.